Study on the Investment Feasibility of the Fishing Boat Considering the Local Wisdom - Syamsul Alam Muchlis; Suandar Baso; Sitti Chairunnisa (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Indonesia Government through the Ministry of Maritime Affairs and Fisheries is holding a fishery boat procurement assistance program of gross tonnage (GT) 5 to 30. In order to be effective investment for the program, a comprehensive study on fishing boat is emphasized to be carried out. This study aims to determine the investment components of a fishing boat with GT of 12, 21 and 30 based on the consideration of the local content, determine the feasibility of fishing boats investment including the local content aspect, and determine the weight of local content for the investment of fishing boat. The investment feasibilty was analysed by using Net Present Value (NPV) and Internal Rate of Return (IRR). In the present results, the three fishing boat sizes of GT 12, 21, and 30 were economic feasibility and suitable in order to support the welfare of fishermen in Sinjai Regency, South Sulawesi Province. The NPV and IRR within 10 years for the fishing boat size of GT 12 are approximately 823 million rupiahs and 77% respectively, 988 million rupiahs and IRR of 54% for GT 21, and 979 million rupiahs and 38% for GT 29. The weight of the local content aspect contributes in average of 81.47% on the investment of the fishing boat wherein the local content includes boat hull buliding, fishing equipment, and labor cost. In addition, the weight of the local content aspect for ship operation is average of 61.88% wherein the local content includes fishermen salary and fishing aggregating device.